2012
DOI: 10.1002/app.35468
|View full text |Cite
|
Sign up to set email alerts
|

Development of nanostructured polyaniline–titanium dioxide gas sensors for ammonia recognition

Abstract: The performance at room temperature of nanostructured polyaniline (PANi)-titanium dioxide (TiO 2 ) ammonia gas sensors was investigated. The PANi-TiO 2 thin-film sensors were fabricated with a spin-coating method on glass substrates. PANi-TiO 2 (0-50%) sensor films were characterized for their structural, morphological, optical, and various gas-sensing properties. The structural analysis showed the formation of nanocrystalline TiO 2 , whereas PANi exhibited an amorphous nature. Morphological analysis of the PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 18 publications
(23 reference statements)
2
38
0
Order By: Relevance
“…A hybrid material particularly suitable for NH 3 recognition based on nanostructured polyaniline and titanium dioxide [PANi-TiO 2 ] has been recently proposed and characterized by morphological analysis by Pawar et al [57]. The response at room temperature of different oxiding and reducing gases of PANi-TiO 2 film is shown in Fig.…”
Section: Pani-based Gas and Vapour Sensorsmentioning
confidence: 98%
“…A hybrid material particularly suitable for NH 3 recognition based on nanostructured polyaniline and titanium dioxide [PANi-TiO 2 ] has been recently proposed and characterized by morphological analysis by Pawar et al [57]. The response at room temperature of different oxiding and reducing gases of PANi-TiO 2 film is shown in Fig.…”
Section: Pani-based Gas and Vapour Sensorsmentioning
confidence: 98%
“…exhibited good sensitivity with the detection level up to 6 ppm, but the response time is up to 10 min, moreover, the sensor didn't show a good selectivity. Pawar et al [17] reported a nanostructured polyaniline-titanium dioxide gas sensor for ammonia recognition. The sensor showed a good selectivity to ammonia, but the detection level was as low as 20 ppm ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…A possible mechanism for the selectivity to NH 3 is the chemisorption of NH 3 on PANI in In 2 O 3 /PANI-2 forming ammonium [32]. Besides, the different gases show different electron affinity values [33], and the varying sensitivity of In 2 O 3 /PANI-2 nanofibers to different gases may be explained by this.…”
Section: Resultsmentioning
confidence: 99%